X-ray and optical characterization of the intermediate products in the Au3+ reduction process by oleylamine. (October 2020) - Kirichkov, Mikhail V.; Guda, Alexander A.; Budnyk, Andriy P.; Bugaev, Aram L.; Lastovina, Tatiana A.; Shapovalov, Victor V.; Guda, Sergey A.; Trigub, Alexander L.; Rusalev, Yuri V.; Chernyshev, Anatoly V.; Lamberti, Carlo; Soldatov, Alexander V.
Abstract: Formation of gold nanoparticles (NPs) from the mixture containing NaAuCl4 as a precursor, octadecene as a solvent and oleylamine as a reducing agent was studied in situ by means of optical and X-ray spectroscopies. Dynamic light scattering (DLS) revealed the presence of initial aggregates of 500 nm average size which split into nanoparticles of about 8 nm width shortly after the reduction from Au 3+ to Au + has been completed. Based on Density Functional Theory (DFT) simulations and analysis of X-ray absorption spectra (XAS) we identified the structure of Au 3+ and Au + gold complexes. Quantitative analysis shows that Au NPs formation proceeds in following steps: substitution of chlorine ligands in Au 3+ complex by four oleylamines; reduction of Au 3+ to Au + coordinated by two oleylamines. Latter process occurs in oleylamine micelles in octadecene. The third step is a fragmentation of large micelles into smaller ones shortly after reduction Au 3+ to Au +, and subsequent slow growth of Au NPs via reduction of Au + to Au 0 . Highlights: Initial agglomerates are split into small 8 nm particles during the reduction of Au. Au(III) complex is coordinated by four N located at 2.04 Å. Au(I) complex is coordinated by two N atoms at 2.05 Å. No Cl atoms are present in the first coordination of Au at all stages of nanoparticle formation.